O serviço de acolhimento em família acolhedora e o direito à convivência familiar e comunitária: uma análise da atuação do poder judiciário. - Corrêa, Izabelle Larocca (2023)
The master's thesis entitled "The Foster Care Service and the Right to Family and Community Coexistence: An Analysis of the Performance of the Judiciary" aims to investigate how the Judiciary guarantees family and community coexistence for children who are welcomed into welcoming families. Initially, the research addresses the condition of subject of rights acquired by children and adolescents since the promulgation of the 1988 Federal Constitution, with an emphasis on the right to family and community coexistence as a fundamental right in light of constitutional principles. The study delimits the current paradigm of the Rights of Children and Adolescents in Brazil, highlighting the foster care service as an alternative to guarantee this right, the responsibility of which falls on the family, society and the State. The causes of application of the Reception Protection Measure, provided for in the Child and Adolescent Statute, and the modalities of its application are discussed, considering the impacts of prolonged institutional care on the intellectual and physical development of those receiving care. The foster care service is characterized as a public policy that requires alignment between the Executive and Legislative Powers to overcome gaps in its implementation. The Judiciary emerges as a protagonist in implementing the right to family life, demanding a reorganized, interdisciplinary justice system aligned with constitutional principles. The study seeks to highlight the importance of family and community coexistence as a fundamental right for the development of children and adolescents, highlighting the need for energetic action by the Judiciary to mitigate problems related to the absence of parents or guardians in vulnerable situations. The relevance of the topic is highlighted and the need for coordinated actions between the various social and political actors to effectively ensure this fundamental right is highlighted, with the methodology used being based on research into doctrine.